ColombiaTuitionSET: Labeled dataset for exploring socioeconomic status, career selection, and tuition fees at a Colombian public universityMendeley Data - Fernan A. Villa-Garzon; Maria A. Muñoz-Alarcon; John W. Branch-Bedoya (Data in Brief)
This dataset examines the interplay between socioeconomic status and educational outcomes among students at the Universidad Nacional de Colombia. Collected from publicly available data in collaboration with the National Directorate of Information, the dataset includes anonymized records of 3361 students from multiple university campuses during the first semester of 2021. It captures a diverse array of socioeconomic and academic variables, such as family income, residence type, tuition fee, and career choice, providing a unique basis for studying educational access in Colombia.Following authorization from the National Directorate of Information, the dataset underwent a rigorous anonymization and validation process, ensuring data integrity and reproducibility. The data was systematically cleaned and organized to highlight key demographic and socioeconomic variables relevant to student accessibility, persistence, and financial sustainability in higher education.With its detailed structure, this dataset is a valuable resource for policymakers and researchers focused on reducing educational inequalities. It supports analyses that reveal how socioeconomic conditions impact educational pathways, enabling the design of targeted interventions to enhance equity in university access and retention. This dataset contributes significantly to the understanding of educational challenges in Colombian public universities, providing a comprehensive basis for the investigation of the socioeconomic factors that influence students' access to and success in higher education.